Economic ProductRank and Quantum Wave Probability (CSIAM Transactions on Applied Mathematics, 2025)
This note discusses a long debated question whether there is randomness inquantum mechanics or not? Einstein’s view on the question is “God does not throwdice”. Our starting point for the discussion is the classification of products in the economic system, called ProductRank, which seems an analog of the “principal component analysis” in statistics. But the former is much more elaborate than the latter.Interestingly, we find an intrinsic common point among economic system, statisticsand quantum mechanics, which then leads to a successful classification of the products in economy, as well as a mathematical view of “wave probability” in quantummechanics. An application to the algorithm for eigenpair is included.
Keywords: Economics; ProductRank; Hermitizable; quantum mechanics.